The Impact of the Abolition of tax credit on ex-dividend day abnormal returns in the united kingdom (uk) market - Basuki, Hardo (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
The ex-dividend day returns are composed of the capital gains component and the dividends component. This study mainly examines the relationship between the 1997 abolition of the tax-credit and the ex-dividend day abnormal stock returns in the UK market (London Stock Exchange). The 1997 abolition of the tax credit on dividend effectively reduced the income of pension funds and other tax-exempt shareholders who had a strong preference for dividends. This study finds that the ex-day abnormal returns (AR) declined from +0.0580 percent during the pre-abolition periods to -0.1459 percent during the post-abolition periods. This decline is statistically significant with a t-value of 2.0431. From these results it would appear that the ex-dividend day AR changed following the 1997 abolition of tax credits on dividends. Moreover the comparison tests of ex-day drop-off ratios between pre-and post-abolition periods show that drop-off ratios for all dividend yield groups increased significantly from 0.519 in the pre-abolition periods to 0.574 over the post-abolition periods with a t-value of 2.183. Thus, the decrease on ex-day AR was further supported by a significant increase in the average price-drop to dividend ratios.The decline in the ex-day AR for the post-abolition periods seems to be driven primarily by quintile 5 (the highest dividend yield quintile). Quintile 5 exhibits strong dividend preference and this preference is likely causedÂ by theÂ imputation system that provides a tax advantage to the tax exempt shareholders. This finding appears to suggest that the highest dividend yield securities are likely to be held by tax-exempt investors such as pension funds that were affected by the abolition of the tax credits on dividend.